2018
DOI: 10.1111/acel.12842
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated homeostatic pathways in sarcopenia among frail older adults

Abstract: Sarcopenia, a core feature of the physical frailty syndrome, is characterized by multisystem physiological dysregulation. No study has explored qualitatively the hierarchical network of relationships among different dysregulated pathways involved in the pathogenesis of sarcopenia. We used 40 blood biomarkers belonging to community‐dwelling prefrail and frail older persons to derive measures of multiple physiological pathways, and structural equation modeling to generate path network models of the multisystem p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 30 publications
0
15
0
2
Order By: Relevance
“…Also, although oxidative stress leads to muscle hypertrophy, chronic stress mediated by the HPA axis, leads to the opposite direction (82)(83)(84)(85). Indeed, alterationsof the HPA axis disrupt the metabolism of the muscle tissue, toward a negative balance between protein generation and degradation, eventually leading to muscle mass loss (86)(87)(88)(89).…”
Section: Associations Between Improved Mood States and Body Compositimentioning
confidence: 99%
See 2 more Smart Citations
“…Also, although oxidative stress leads to muscle hypertrophy, chronic stress mediated by the HPA axis, leads to the opposite direction (82)(83)(84)(85). Indeed, alterationsof the HPA axis disrupt the metabolism of the muscle tissue, toward a negative balance between protein generation and degradation, eventually leading to muscle mass loss (86)(87)(88)(89).…”
Section: Associations Between Improved Mood States and Body Compositimentioning
confidence: 99%
“…Indeed, alterationsof the HPA axis disrupt the metabolism of the muscle tissue, toward a negative balance between protein generation and degradation, eventually leading to muscle mass loss (86)(87)(88)(89). Conversely, impaired HPA axis also leads to concurrent independent body fat gain (84), as multiple mechanisms mediated by the HPA axis induce increase of fat cell size and induce a pro-inflammatory status irrespective of caloric balance, proportion of macronutrient intake, and sleeping patterns, since a post-receptor modification from cortisone to cortisol by enhanced activity of 11betahydroxysteroid dehydrogenase type 1(11beta-HSD1) (90,91). In addition,disruption of the muscle metabolism, herein induced by altered cortisol regulation, has also demonstrated to have direct effects on the metabolism and accumulation of fat (92).…”
Section: Associations Between Improved Mood States and Body Compositimentioning
confidence: 99%
See 1 more Smart Citation
“…IGF-1 participates in muscle anabolism via Akt phosphorylation activating the mammalian target of rapamycin (mTOR) pathway which ultimately controls muscle protein synthesis and turnover [ 27 ]. Sarcopenia results from a decrease in muscle anabolic pathways with an increase in catabolic pathways [ 28 ]. For sarcopenic individuals, Kwak et al [ 21 ] observed a significant (further) decrease in serum IGF-1 from 72.61 ± 5.49 ng/mL to 58.16 ± 3.37 ng/mL compared to the non-sarcopenic control group of similar age.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is mainly caused by structural changes, such as loss of muscle fibers and reduction in their size, lower ratio of fast (type II) to slow (type I) muscle fibers, adipose and fibrotic tissue infiltrations [8][9][10], and muscular mass loss, that occur with aging. The process may be accelerated and worsened by a sedentary lifestyle, poor nutritional status [11], and chronic diseases that cause inflammation [12] along with hormonal and metabolic dysregulations [13].…”
Section: Introductionmentioning
confidence: 99%